Environmental effects on the genetic architecture of fitness components in a simultaneous hermaphrodite. Issue 1 (27th October 2021) - Janicke, Tim; Chapuis, Elodie; Meconcelli, Stefania; Bonel, Nicolas; Delahaie, Boris; David, Patrice
Abstract: Understanding how environmental change affects genetic variances and covariances of reproductive traits is key to formulate firm predictions on evolutionary responses. This is particularly true for sex‐specific variance in reproductive success, which has been argued to affect how populations can adapt to environmental change. Our current knowledge on the impact of environmental stress on sex‐specific genetic architecture of fitness components is still limited and restricted to separate‐sexed organisms. However, hermaphroditism is widespread across animals and may entail interesting peculiarities with respect to genetic constraints imposed on the evolution of male and female reproduction. We explored how food restriction affects the genetic variance–covariance (G) matrix of body size and reproductive success of the simultaneously hermaphroditic freshwater snail Physa acuta . Our results provide strong evidence that the imposed environmental stress elevated the opportunity for selection in both sex functions. However, the G–matrix remained largely stable across the tested food treatments. Importantly, our results provide no support for cross‐sex genetic correlations suggesting no strong evolutionary coupling of male and female reproductive traits. We discuss potential implications for the adaptation to changing environments and highlight the need for more quantitative genetic studies on male and female fitness components in simultaneous hermaphrodites. Abstract : Experimental study suggests that environmental stress affects the opportunity for selection but not the genetic variance–covariance matrix of male and female reproductive performance in a simultaneous hermaphrodite.